PENERAPAN MODEL DISCOVERY LEARNING (DL) MENGGUNAKAN PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA SMA TARUNA PEKANBARU T.P 2015/2016 - Lorenza, Melti; Natalina, Mariani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to improve learning outcomes biology class XI Science SMA Taruna Pekanbaru through the implementation model of Discovery Learning (DL) using the Concept Map, the research was conducted in SMA Taruna Pekanbaru in April-May 2016. The parameters measured were the result study of cognitive, affective and psychomotor. The methods of this research was classroom action research. It had been done in two cylce. There were planning step, acting step, observation step and reflection step for each cycle. The research instrument used was learning devices and data collection instruments. The data obtained were analyzed descriptively. The results of this study indicate the cognitive aspects of daily tests first cycle that 80.97 (Enough) increased in the second cycle into 84.67 (enough). Students who complete the first cycle of 27 students (89.91%) and the second cycle is 27 students (89.91%). While the average aspect of attitude in the first cycle that 67.40 (Less) and increased in the second cycle into 87.19 (Good). Furthermore, the average in the first cycle that psychomotor aspects 78.90 (Enough) and increased in the second cycle into 91.81 (good). Based on these data we can conclude that the application of the model of Discovery Learning (DL) using Concept Maps can improve learning outcomes biology class XI Science Senior High School Taruna Pekanbaru.